Realizing highly efficient blue photoluminescence of dimethylsilane-aryl (phenylene, diphenylene, fluorenyl) main-chain polymers with σ–π conjugation. Issue 13 (8th March 2022) - Huang, Wenyan; Zhu, Yeqi; Zhong, Lei; Jin, Chao; Zheng, Yinong; Zhang, Yinggan; Lan, Siqi; Gong, Shiwen; Zhao, Jiangnan; Huang, Meng; Yao, Rongqian
Abstract : Flexible blue-emitting polyfluorenecarbosilane with an integrated high quantum yield (up to 89.75%) and easy film-forming ability was successfully synthesized. Abstract : Designing deep-blue emitting materials with integrated high quantum yields and easy film-forming ability is challenging. As a typical organosilicon polymer, polycarbosilane (PCS) with a –Si–C– repeated backbone has received much attention owing to its high stability, versatile optical properties, easy solubility and film-forming ability. Herein, an ingenious strategy toward enhanced photoluminescence characteristics was successfully introduced to obtain a series of σ–π conjugated PCS containing dimethylsilane-aryl (phenylene, diphenylene, fluorenyl) backbones via the Grignard reaction. Such synergistic effects of –Si–C– and aryl endow the products with high quantum yields and easy large-size forming ability in a simple and economical manner. Particularly, polyfluorenecarbosilane (PFCS) exhibits excellent deep-blue light emission ( λ max = 414 nm) with a high quantum yield (up to 89.75%), which is the highest value ever reported for organosilicon polymers to the best of our knowledge. It is demonstrated that the findings offer new opportunities for the development of flexible, foldable and stretchable organic devices.